Monitoreo del trips de la flor del banano frankliniella sp thysanoptera thripidae en la finca la sabana - Zambrano Loyola, Herman De Jesus (2015)
Medium and small bananas producers in El Oro province face the rejection of their production due to pests attacks affecting the fruit quality and the banana trade. One of these pests is the banana flower thrips Frankliniella sp. which directly affects the banana flower when begins to emerge, causing damages two weeks after bagging. The general objective of the research was determining the populations of Frankliniella sp. in 3 parcels in the banana farm La Sabana, using the visual method in the banana farm of one year and a half of planted, located in La Peaña Pasaje., in the research we found the number of thrips in the banana flower of two weeks after bagging, in the farm also also took data of temperatura and relative humidity, the spacial distribution of the thrips was aggregate, grouping most of the thrips in the parcel 2 with a total number of 5183, followed by the parcels 3 and 1, with 5073 and 4805 thrips, respectively, a higher average of 41,5 thrips in parcel 3, in addition we was able to identificate that the thrips specie was Frankliniella sp. using the identification keys for thrips species.